2020
DOI: 10.1073/pnas.2001560117
|View full text |Cite
|
Sign up to set email alerts
|

Basal ganglia beta oscillations during sleep underlie Parkinsonian insomnia

Abstract: Sleep disorders are among the most debilitating comorbidities of Parkinson’s disease (PD) and affect the majority of patients. Of these, the most common is insomnia, the difficulty to initiate and maintain sleep. The degree of insomnia correlates with PD severity and it responds to treatments that decrease pathological basal ganglia (BG) beta oscillations (10–17 Hz in primates), suggesting that beta activity in the BG may contribute to insomnia. We used multiple electrodes to record BG spiking and fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 53 publications
10
40
0
Order By: Relevance
“…It remains unknown how this finding compares with control subjects and whether the presence or absence of an identifiable subcortical beta peak in NREM correlates with any sleep‐related symptoms. However, studies in primate models suggest that increased STN beta power in NREM sleep may be associated with insomnia severity 102 . In a 1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine primate model, both a decrease in slow oscillatory activity and an increase in beta oscillations in the basal ganglia nuclei were seen during NREM sleep (Fig.…”
Section: Subcortical Electrophysiological Recording In Pd During Sleepmentioning
confidence: 95%
“…It remains unknown how this finding compares with control subjects and whether the presence or absence of an identifiable subcortical beta peak in NREM correlates with any sleep‐related symptoms. However, studies in primate models suggest that increased STN beta power in NREM sleep may be associated with insomnia severity 102 . In a 1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine primate model, both a decrease in slow oscillatory activity and an increase in beta oscillations in the basal ganglia nuclei were seen during NREM sleep (Fig.…”
Section: Subcortical Electrophysiological Recording In Pd During Sleepmentioning
confidence: 95%
“…In the present study, we investigated whether the reduction in SWS was due to a decrease in the number and/or duration of the episodes, but no significant differences between the groups were observed. Also, we demonstrated that rotenone administration altered the power spectrum within different frequency bands, which was also observed with 1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine (MPTP) administration (Mizrahi‐Kliger, Kaplan, Israel, Deffains, & Bergman, 2020), but not in the 6‐hydroxydopamine (6‐OHDA) animal model (Cavelli et al., 2019).…”
Section: Discussionmentioning
confidence: 70%
“…Moreover, natural nocturnal sleep has been found to be markedly disturbed following surgical procedures 41 . Disturbances of sleep are highly prevalent in basal ganglia-related neurodegenerative disorders, particularly PD [42][43][44] . Enabling a more restful sedation could greatly benefit these patients who already suffer from sleep difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…The EOG, EMG and EEG were sampled at 2750 Hz. Detailed polysomnography methods can be found here 44 .…”
Section: Polysomnographymentioning
confidence: 99%